2012 International Conference on Lightning Protection (ICLP) 2012
DOI: 10.1109/iclp.2012.6344372
|View full text |Cite
|
Sign up to set email alerts
|

Total lightning observations to wind turbines

Abstract: In summer 2011 a new VHF Lightning Mapping Array was installed at the northeast of Spain. In that area a VHF interferometer and a VLFILF lightning detection networks are also operative. The close presence of wind farms in the area of the Lightning Mapping Array showed some lightning activity not reported before. This paper describes the observations and discusses the possible effects to the wind turbine lightning protectionPostprint (published version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The former is aimed to intercept the lightning leaders, whereas the latter is intended to conduct the lightning current from the attachment point to the earthing system [11], [12]. The receptors have to be designed according to the procedures specified in the IEC standard [12] to transfer most of the lightning energy to the DC and avoid damage [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The former is aimed to intercept the lightning leaders, whereas the latter is intended to conduct the lightning current from the attachment point to the earthing system [11], [12]. The receptors have to be designed according to the procedures specified in the IEC standard [12] to transfer most of the lightning energy to the DC and avoid damage [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Over more than a decade, several studies [1][2][3][4][5] have shown that wind turbine blades are highly susceptible to downward lightning strikes, as well as to triggering upward lightning. Consequently, it is required to equip them with a lightning protection system (LPS) capable of preventing damage due to lightning direct attachment.…”
Section: Introductionmentioning
confidence: 99%
“…The receptors have to be designed according to the guidelines and procedures specified in the IEC standard [7]. In this case, most of the lightning energy is discharged to the ground through the LPS [3,5].…”
Section: Introductionmentioning
confidence: 99%